A case of rapidly progressing and poorly differentiated Ip‐type early‐stage colorectal adenocarcinoma. Issue 1 (26th October 2022) - Tsubomoto, Atsuko; Sashiyama, Hiroshi; Koike, Junichi; Morita, Yohei; Tsutsumi, Osamu; Hamahata, Yukihiro
Abstract: A 36‐year‐old woman visited our hospital with a chief complaint of bleeding during defecation. Colonoscopy revealed a 20‐mm pedunculated polyp in the sigmoid colon, which was en bloc resected under endoscopy. The histopathological diagnosis was adenoma cancer with a depth of invasion indicating mucosal cancer, no lymphovascular invasion, and negative at the resection margin. The poorly differentiated adenocarcinoma component comprised approximately 5% of the tumor. Although there were no recurrence signs in the computed tomography scans obtained 4 months post polypectomy, the patient experienced aggressive lower back pain at 6 months post polypectomy. Local recurrence, peritoneal dissemination, and liver metastasis were confirmed. Finally, the patient died following a rapid and aggressive deterioration of her general condition. Histological examination of the local recurrence revealed a poorly differentiated adenocarcinoma (por2), with immunostaining revealing a high Ki67 positivity rate of 95%. Moreover, the poorly differentiated adenocarcinoma region of the resected polyp had a Ki67 positivity rate of 90%, which suggested that they were the same tumors. These findings suggested that the recurrence could have occurred through implantation.